1978
DOI: 10.1530/jrf.0.0530019
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastructural study of the human micropolycystic ovary

Abstract: The basement membrane of follicles in the micropolycystic ovaries of infertile women was thickened compared to that in the ovaries of normal women or those with typical polycystic ovaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Previous studies have defined ultrastructural changes in follicular cells in PCOS ( 20 , 21 , 22 ); however, prior to the present study, no study identifying which stages of folliculogenesis exhibit these ultrastructural changes in PCOS had existed. In this study, we showed irregularities and thickening and ondulation in the basement membrane of granulosa cells in most of the multilaminar and secondary follicles in the PCOS group.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have defined ultrastructural changes in follicular cells in PCOS ( 20 , 21 , 22 ); however, prior to the present study, no study identifying which stages of folliculogenesis exhibit these ultrastructural changes in PCOS had existed. In this study, we showed irregularities and thickening and ondulation in the basement membrane of granulosa cells in most of the multilaminar and secondary follicles in the PCOS group.…”
Section: Discussionmentioning
confidence: 77%